A User-Centered Approach to Designing Secondary Anesthesia Medication Labels. (September 2022) - Goel, Swati; Joseph, Anjali; Neyens, David M.; Catchpole, Kenneth; Alfred, Myrtede; Jaruzel, Candace; Tobin, Catherine; Aberathy, James H; Heinke, Timothy; Haney, Jason
Poorly designed and implemented medication labels have been identified as a source of medication errors within anesthesia delivery. Previous studies noted that simplified text and icons are useful in warning labels used for prescription drugs, especially for people with low literacy levels. In addition, Tallman lettering can reduce errors due to the custom capitalization of text. However, icons, color, and Tallman lettering have not been explored for improving the readability of anesthesia medication labels. This study utilizes a user- centered approach to design and evaluate icons and other graphical features to be included on secondary medication labels placed on infusion bags within anesthesia point-of-care. The study utilizes an iterative design process to examine the potential efficacy of these design characteristics by evaluating them with the anesthesia providers/clinicians through an online survey. Findings suggest that introducing graphical components like icons and color may be useful and accepted by clinicians to improve medication recognition.